2010
DOI: 10.1007/s11224-010-9586-x
|View full text |Cite
|
Sign up to set email alerts
|

The tunability of the electronic structures for poly(carbosilylsilanes): a theoretical study

Abstract: To tune purposefully the electronic structures of poly(carbosilylsilanes), a theory study has been investigated using the density functional theory combined with AM1 method. Attentions were paid to the dependence of molecular geometries and absorption spectra on the backbone conformation and the various substituting groups. The strong electronegative substituents can more effectively tune the geometries and spectra of the polysilanes than the alkyl ones. Their main-chain substitutions can induce the great red-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Geometric and electronic changes of a series of poly(carbosilysilanes) induced by varying the size and species of the substituting groups was investigated by Ding et al [156] using DFT combined with AM1 method. While the bias-trans conformation is preferred if the side chain contains fewer than three carbons, the all-trans conformation with a loose-helix backbone is a preference with more than four carbons in side chain.…”
Section: Issuementioning
confidence: 99%
“…Geometric and electronic changes of a series of poly(carbosilysilanes) induced by varying the size and species of the substituting groups was investigated by Ding et al [156] using DFT combined with AM1 method. While the bias-trans conformation is preferred if the side chain contains fewer than three carbons, the all-trans conformation with a loose-helix backbone is a preference with more than four carbons in side chain.…”
Section: Issuementioning
confidence: 99%
“…The close relationship between the structural and the optical property of polysilane is evident from a number of experimental and theoretical studies devoted to tailoring the bandgaps of polysilanes by manipulating the backbone conformations or the side-chain substitutions [22][23][24][25][26][27]14,28]. It has been shown that the bandgap of polysilanes and their derivatives increase as the Si backbone conformation becomes more twisted.…”
Section: Introductionmentioning
confidence: 99%